AB1043 Rheumatoid factor isotypes – still an useful tool in the diagnosis of rheumatoid arthritis?. (15th June 2017) - Guerra, M; Vieira, R; Cruz, AP; Videira, T; Pinto, P
Abstract : Background: Rheumatoid factor (RF) and anti-citrullinated peptide antibodies (ACPA) are key serologic markers in the diagnosis of Rheumatoid Arthritis (RA) included in the 2010 ACR/EULAR diagnostic criteria. Determination by enzyme-linked immunosorbent assay (ELISA) allows RF isotypes' quantification (IgG, IgA and IgM), improving diagnostic accuracy 1, 2 . Objectives: To assess the clinical value of RF-IgG/IgA/IgM (ELISA) in the diagnosis of RA, in comparison to RF-IgM (nephelometry). Methods: A population of RA outpatients fulfilling the 2010 ACR/EULAR diagnostic criteria was cross-sectionally evaluated. Data on demographic and clinical characteristics was collected. RF-IgG / IgA / IgM (ELISA, Orgentec®), RF-IgM (nephelometry, Siemens®) and ACPA-IgG (ELiA, ThermoFisher®) were measured. Values three times or more above the upper limit of normal were considered high-positive (in agreement to 2010 ACR/EULAR diagnostic criteria). Results: A total of 87 patients (70.1% female) were included, with a mean (SD) age of 57.3 (12.29) years. Median time of disease evolution was 6 years, ranging from 0 to 37 years. Erosions were present in 50.6% (N=44). RF-ELISA was positive (at least one isotype increased) in 85.1% (N=74); the most frequent isotype was IgM (70.1%;N=61) and the most frequent combination was IgG, IgA and IgM positivity (46.0%;N=40) (table1 ). FR-nephelometry and ACPA were positive in 58.6% (N=51) and 47.1% (N=41), respectively. Comparing the two RF methods, 56.3% (N=49) were both RF-nephelometry and RF-ELISA positive; 28.7% (N=25) were RF-ELISA positive and RF-nephelometry negative, and only 2.3% (N=2) verified the opposite (p=0.001). As for RF high-positivity, 4.6% (N=4) of the 87 patients were only RF-nephelometry high-positive, 9.2% (N=8) only RF-ELISA high-positive and 34.5% (N=30) both high-positive (p<0.001). In the RF-nephelometry negative population (N=36), ACPA and RF-ELISA were both positive in 11.1% (N=4). Only 8.3% (N=3) were solely ACPA positive and 58.3% (N=21) solely RF-ELISA positive, however without statistical significance. Considering the ACPA negative population (N=46), 32.6% (N=15) were both RF positive; 45.7% (N=21) were RF-ELISA positive and RF-nephelometry negative and 4.3% (N=2) the opposite, without a statistical significance. Conclusions: ELISA is superior to nephelometry detecting RF in patients with RA, as also in quantifying high-positive values. References: Routine measurement of IgM, IgG, and IgA rheumatoid factors: high sensitivity, specificity, and predictive value for rheumatoid arthritis. Swedler W, Wallman J, Froelich CJ, Teodorescu M. J Rheumatol, 1997 Jun;24(6):1037–44. Is rheumatoid factor still a superior test for the diagnosis of rheumatoid arthritis? Singh U, Vishwanath A, Verma PK et al. Rheumatol int, 2010 June; 30(8):1115–9. Disclosure of Interest: None declared